1997
DOI: 10.1159/000201432
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal Acid and Salivary Secretion: Is Chewing Gum a Treatment Option for Gastro-Oesophageal Reflux?

Abstract: The presence of acid in the oesophagus has been shown to stimulate salivary secretion, but the relevance of this oesophago-salivary reflex for acid clearance in physiological and pathological gastro-oesophageal reflux (GOR) is unknown. This study was designed to investigate the interrelation between oesophageal acid and both resting and stimulated salivary secretion. In 10 healthy volunteers, the acid clearance times after bolus infusion of 20 ml of 0.1 N hydrochloric acid were measured by means of ambulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Further, chewing gum after a meal helps to reduce postprandial oesophageal acid exposure 114 . It was also suggested that chewing gum might be a treatment option for some patients with symptomatic reflux 115,116 . For individuals at high risk for erosive tooth wear and those with active erosion, it is suggested that tooth brushing should be postponed after consumption of erosive foodstuffs or beverages, in order to minimise enamel loss.…”
Section: Preventionmentioning
confidence: 99%
“…Further, chewing gum after a meal helps to reduce postprandial oesophageal acid exposure 114 . It was also suggested that chewing gum might be a treatment option for some patients with symptomatic reflux 115,116 . For individuals at high risk for erosive tooth wear and those with active erosion, it is suggested that tooth brushing should be postponed after consumption of erosive foodstuffs or beverages, in order to minimise enamel loss.…”
Section: Preventionmentioning
confidence: 99%
“…However, chewing gum after a meal helps to reduce postprandial esophageal acid exposure [39]. It was also suggested that chewing gum might be a treatment option for some patients with symptomatic reflux [40,41].…”
mentioning
confidence: 99%
“…As described above, the greatest amount of saliva is induced after food intake. This salivation response is initiated by various sensory inputs, including visual, olfactory, oropharyngeal, and esophageal senses (gustatory, mechanical, and thermal) [126]. Afferent nerve impulses from the salivary reflex pass to the salivary nuclei through the medulla oblongata, including the NTS and the parabrachial nucleus (PBN), and these impulses affect the parenchyma of the salivary glands from these centers via the efferent parasympathetic secretomotor nerves [125].…”
Section: The Role Of Salivary Secretions In Eating Disordersmentioning
confidence: 99%